EVALUATION OF PAVEMENT PERFORMANCE ON JALAN RANCAPURUT SUMEDANG USING THE CORE DRILL METHOD - Andre Septian; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2024)
This research aims to comprehensively analyze the current condition and performance of Rancapurut Road in Sumedang, Indonesia. The analysis is conducted to identify areas requiring repair and evaluate the effectiveness of current maintenance and rehabilitation methods. It is crucial to ensure that the region's road infrastructure meets expected safety and comfort standards and to provide recommendations for future improvements. The research employs an exploratory quantitative approach, collecting empirical data directly from the field. The research population includes segments of Rancapurut Road in Sumedang, with samples selected randomly or based on critical areas representing the whole. Primary data collection utilizes core drill techniques, extracting core samples of concrete or asphalt for thickness, composition, and pavement layer condition analysis. Secondary data, such as road maintenance records, is also gathered. The results of the research indicate that the overall condition of the Rancaputu Road pavement is good. The average thickness of the pavement at location 1 is 4.7 cm, location 2 is 4.3 cm, and location 3 is 4.55 cm. However, some points of measurement show lower thicknesses, such as the second measurement point at location 1 (3.25 cm) and the fourth measurement point at location 3 (3.08 cm). The reduction in pavement thickness can be caused by various factors, such as heavy traffic loads, inadequate subgrade conditions, or poor pavement material quality. The research findings are expected to be useful for road managers and engineers in Sumedang and other regions with similar conditions. The findings can be used to improve the planning and implementation of pavement maintenance and rehabilitation programs.